Business power in global governance - Fuchs, Doris A. (New Delhi : Viva Books, 2008)
Has the political power of big business, particularly transnational corporations (TNCs), increased in our globalizing world? What, if anything, constrains TNCs? Analyzing the role of business in the global arena, this book addresses these questions. It also highlights the role of business in framing policy issues and influencing public debate.
Includes bibliographical references and index.
Keywords: International business enterprises -- Political aspects; Globalization; Corporate power; Business and politics